Temperature controls the episodic dynamics of deep slow slip - Zaccaria El Yousfi; Baptiste Rousset; Mathilde Radiguet; William B. Frank (Proceedings of the National Academy of Sciences, 2026)
The deformation regime that accommodates tectonic motion at plate boundaries changes as pressures and temperatures increase with depth, transitioning from the shallow frictional sliding of seismic ruptures to deep, viscous flow. We use recurring swarms of low-frequency earthquakes in this transition zone to measure the recurrence intervals and durations of accompanying slow slip across four plate boundaries. We find these time scales systematically decrease with depth and linearly scale with one another. Assuming a transition zone governed by episodic faulting, the observed time scales produce an average slow slip rate of 7 ± 2 mm/d across all four plate boundaries that is independent of depth. Thermal models place these slow slip dynamics within a common, narrow range of temperatures. Our results suggest deep slow slip is the result of the episodic unjamming of the plate boundary by frictional heterogeneities whose relaxation is modulated by surrounding temperature-dependent viscous material.